Концепт української держави в поглядах М. Грушевського - Поцюрко, О. Ю.; Potsyurko, O. Yu. (My University, 2017)
У статті обґрунтовується ідея про те, що головним ідейним підґрунтям, яке сформувало концепцію української державності М. Грушевського, було ототожнення національної й соціальної ідеї. Учений був причетний до створення фактологічного підґрунтя філософії української ідеї, очоливши національно-демократичний напрям тлумачення української ідеї й історичних шляхів її розвитку. Говорячи про федеративний устрій майбутньої Росії та орієнтуючись на революційні настрої в Російській імперії, наслідком яких мала стати відмова від обмеження свободи слова, зборів і організацій, мислитель наголошує на тому, що програма-мінімум українства – широка автономія, а програма-максимум – федерація й «неповна самостійність». Сподіваючись на наявність усіх прав і свобод, які притаманні країнам західного світу (до них дослідник зараховував і Україну), українцям було необхідно продемонструвати толерантне ставлення до нацменшин, залучивши їх до місцевого самоврядування.

В статье обосновывается идея о том, что главным идейным основанием, которое сформировало концепцию украинской государственности М. Грушевского, было отождествление национальной и социальной идеи. Ученый был причастен к созданию фактологического основания философии украинской идеи, возглавив национально-демократическое направление толкования украинской идеи и исторических путей ее развития. Говоря о федеративном устройстве будущей России и ориентируясь на революционные настроения в Российской империи, следствием которых должен был стать отказ от ограничения свободы слова, собраний и организаций, мыслитель отмечает, что программой-минимум украинства является широкая автономия, а программой-максимум – федерация и «неполная самостоятельность». Надеясь на наличие всех прав и свобод, присущих странам западного мира (к ним исследователь относил и Украину), украинцам необходимо было продемонстрировать толерантное отношение к нацменьшинствам, привле- кая их к местному самоуправлению.

The article substantiates the idea that the main ideological basis that formed the concept of Ukrainian statehood of M. Hrushevsky was the identification of the national and social idea. The scholar was involved in the creation of a factual basis for the philosophy of the Ukrainian idea, leading the national-democratic direction of the interpretation of the Ukrainian idea and historical ways of its development. Speaking about the federal structure of the future of Russia and focusing on the revolutionary sentiment in the Russian empire, the consequence of which was the refusal to restrict freedom of speech, assembly and organizations, the thinker emphasized that the program has a minimum of Ukrainians with broad autonomy, and the maximum program is a federation and “incomplete independence”. Hoping for the existence of all the rights and freedoms inherent in the countries of the Western world (to which the researcher also counted Ukraine) Ukrainians need to demonstrate a tolerant attitude towards national minorities by involving them in local self-government.

The article substantiates the idea that the main ideological basis that formed the concept of Ukrainian statehood of M. Hrushevsky was the identification of the national and social idea. The scholar was involved in the creation of a factual basis for the philosophy of the Ukrainian idea, leading the national-democratic direction of the interpretation of the Ukrainian idea and historical ways of its development. Speaking about the federal structure of the future of Russia and focusing on the revolutionary sentiment in the Russian empire, the consequence of which was the refusal to restrict freedom of speech, assembly and organizations, the thinker emphasized that the program has a minimum of Ukrainians with broad autonomy, and the maximum program is a federation and “incomplete independence”. Hoping for the existence of all the rights and freedoms inherent in the countries of the Western world (to which the researcher also counted Ukraine) Ukrainians need to demonstrate a tolerant attitude towards national minorities by involving them in local self-government.
Поцюрко О. Ю. Концепт української держави в поглядах М. Грушевського / О. Ю. Поцюрко // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 20. - С. 97-100.
Keywords: українське питання; українська держава; нація; автономність; Михайло Грушевський; украинский вопрос; украинское государство; нация; автономность; Михаил Грушевский; Ukrainian question; Ukrainian state; nation; autonomy; Mykhaylo Hrushevsky